Feresa Gray 1870 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Feresa Gray 1870 Feresa Gray 1870, Proc. Zool. Soc. Lond., 1870 (1): 77. Type Species: Delphinus intermedius Gray 1827 Species and subspecies: 1 species: Species Feresa attenuata Gray 1874 Discussion: Delphinus intermedius Gray, 1827 was preoccupied by Delphinus intermedius Harlan, 1827 (= Globicephala melas ). Gray subsequentally changed generic designations of that nominal taxon ( Grampus intermedius Gray, 1843; Orca intermedia Gray, 1846). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 728, DOI: 10.5281/zenodo.7316519